DEVELOPMENT OF THE COGNITIVE ACTIVITY OF FUTURE TEACHERS IN INNOVATIVE EDUCATIONAL CONDITIONS AS A SOCIAL PEDAGOGICAL NECESSITY - Yuldasheva Malohat Erkinovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides an insight into the theoretical basis for the development of future teachers' cognitive activities in innovative educational settings. The article explains the theories of famous philosophers and didactics on cognition. The importance of using active learning methods in the development of cognition activities in future teachers has been touched upon.